Penggunaan Website Wordwall Sebagai Media Pembelajaran Untuk Meningkatkan Motivasi Belajar Siswa di SMK Bima Utomo - Tigor Sitohang; Eva Dita Yanti Simanjuntak; Sarah Evelyn Samosir; Mindela Frida Panggabean; Sarah Evelyn Simanjuntak (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
A teaching program is a plan for implementing the teaching and learning process which is based on consideration of the objectives to be achieved, materials, methods, tools, time allocation and evaluation so that students master the learning process and have optimal learning outcomes. Wordwall is an interactive media that provides features to foster student learning motivation according to the learning material presented by the teacher in class. Word wall media provides features such as quizzes, matching, pairing, anagrams, random words, word searches, grouping. The PkM (Community Service) Lecture Program with the title